Karşılıksız çek keşide etme suçu ve bankaların 3167 sayılı kanuna dayalı ceza sorumlulukları - Döner, İsa (My University, 2002)
İnceleme konusu bir malı haksız olarak elinde bulunduran kişinin, bu malı iade etmesidir. Bu malı iade sırasında söz konusu olabilecek sorumluluk düzenidir. Bu sorumluluk düzeninin yürürlük kazanabilmesi için öncelikle temel bir iade talebinin bulunması gereklidir. Medenî Kanunumuzun 993-995. Maddeleri bu temel iade talebine bağlı olarak yürürlük kazanacak olan ve malı iade etmekle yükümlü olan kişiyi sorumlu tutan yan talepleri düzenler. Aynı zamanda malı iade etmek zorunda kalan kişinin bu mala yaptığı giderleri hangi ölçüde talep edebileceğini belirlerler. Giderlere yönelik bu talep hakkını, giderlere bağlı karşı hak olarak değerlendirebiliriz. Malı haksız olarak elinde bulunduran ve iade etmek zorunda kalan kişinin sorumluluğunda önemli olan nokta iyi niyetli veya kötü niyetli olmasıdır. İyi niyetli olması haksız olduğunu bilmemesi ve bilmesini gerekli kılan bir durumun olmaması demektir. Malı haksız olarak elinde bulunduran kişi, iyi niyetli olduğu takdirde mala gelen zararlardan ve elde ettiği ürünlerden ötürü sorumlu tutulamayacaktır. Bir başka deyişle malı kendisinde bulunduğuna iyi niyetle inandığı hakka uygun olarak kullandığı takdirde sorumsuzluk ayrıcalığına sahiptir. Ne var ki, istisnaî olarak, sebepsiz zenginleşme kurallarının müdahalesi söz konusu olabilir. Örneğin malı bir başkasına devir sonucu bir karşılık elde etmişse bu karşılığı gerçek hak sahibine aktarmak zorunda kalabilir. Veya malın özünü, cevherini tahrip ederek bir kazanç sağlamışsa, kendisinden bu kazanç istenebilir. Öte yandan, malı haksız olarak elinde bulunduran kişi iyi niyetli ise, malı iade ederken, mala yapmış olduğu zorunlu ve yararlı giderleri talep edebilir. Bu giderler kendisine karşılanıncaya kadar malı iade etmekten kaçınabilir. Diğer giderleri talep edemez, fakat, bu giderlerle mala eklediği şeyleri, mala zarar vermemek kaydıyla ayırıp alabilir. Malı haksız olarak elinde bulunduran kişi kötü niyetli ise, malı iade etmek konusundaki ana yükümlülüğü yanında, bazı yan yükümlülükleri de olacaktır. Örneğin malın özüne, cevherine zarar vermişse bu zararlardan kusuru olmasa bile sorumlu olacaktır. Ayrıca malı haksız olarak elinde bulundurmasından ötürü gerçek hak sahibinin uğradığı bütün zararları da kusuru olmasa bile karşılamak zorunda kalacaktır. Maldan elde ettiği semereleri gerçek hak sahibine iade etmelidir. Bu semereler artık mevcut değillerse parasal karşılıklarını gerçek hak sahibine ödemelidir. Öte yandan elde etmeyi ihmal ettiği semereleri de gerçek hak sahibine karşılamalıdır. Bu konuda tıpkı bir idareci-vekil gibi sorumludur. Yani dikkatli ve özenli bir idareci-vekil, özenli bir idare sonucunda objektif olarak ne kadar semere elde edecekse, bu semereleri elde etmeyi ihmal ettiği takdirde sorumlu olacaktır. Bu sorumluluk için de kusurlu olması gerekmez. Öte yandan, gerçek hak sahibinin bu ihmal edilen semereleri elde etmek niyetinde olup olmadığına da bakılmaz. Nihayet, malı bizzat kullanmasından ötürü de sorumlu olacaktır. Malı bizzat kullanması neticesinde de kullanma karşılığı ödemelidir. Bu sorumluluk her ne kadar Medenî Kanunun 995. Maddesinde açık olarak düzenlenmemişse de, 993. Maddenin zıt anlamından çıkmaktadır. Malı haksız olarak elinde bulunduran kişi eğer kötü niyetli ise, sadece zorunlu giderlerini isteyebilir. Bunun için de bu zorunlu giderler gerçek hak sahibinin masraftan kurtularak tasarrufta bulunmasına yol açmış olmalıdır. S U M M A R Y The subject of examination is the return of any property, which has been unjustly in the possession of any person, by that person.İt is the order of responsibility which may arise during the return of the property, in order to ensure the validity of this order of responsibility, initially there has to be a basic reguest for return. Articles 993-995 of the Civil Law arrange the subsidiary claims which shall become valid depending on this basic reguest for return and which hold responsible the person liable to return the property. At the same time they determine to which extent the person, who has to return the property, may claim the expenses the latter has made on this property. We may consider this right of claim for expenses as a counter-right depending on expenses. An important point in the responsibility of the person, who has been unjustly in the possession of the property and who has to return it, is that the latter has good intention or evil intention. The fact that the person has good intention means that the latter doesn't know that he/ she is unjust and that there isn't any situation reguiring the person to know his/ her being unjust. İf the person having unjustly possession of the property has good intention, this person may not be held responsible for any damages caused to the property and due to any products this person has obtained. In other words, this person has the privilege of irresponsibility in case the latter uses the property in conformity with the right he/ she believes to have with good intention However, exceptionally, there may be the interference of rules of becoming rich without any reason. For example, if the person has obtained an allowance as a result of the latter's transfering the property to someone else, the person may be obligued to transfer this allowance to the real person entitled. Or if the person has provided any gain by destroying the essence, the substance of the property, then this gain may be reguested from this person. On the other hand, if the person having unjustly possession of the property has good intention,this person may, when returning the property, reguest the compulsory and beneficial expenses the latter has made on the property. The person may avoid returning the property until these expenses have been covered to him/ her. This person may not reguest the other expenses but may remove and take away anyting whice the latter has added to the property provided that no harm is given to the property. İf the person unjustly in possession of the property has evil intention the latter shall also have some subsidiary liabilities along with the main liabilities in terms of returning the property. For instance, if the person has caused harm to the property's essence, its substance , then the latter shall be responsible for these damages even if there isn't any fault on the latter's party. Besides, due to his/ her unjustly use of the property, the latter shall have to cover all losses suffered by the real person entitled even if there isn't any fault on the former's part. This person has to return the profit which the latter has obtained from the property to the real person entitled. İn case these profits are not available any longer, the person has to pay their monetary eguivalents to the real person entitled. On the other hand,this person shall also cover the profits which the latter neglected to obtain to the real person entitled. İn this regard,this person shall he responsible guite like an administrator-representative. That is to say that the extent of profit Which an attentive and careful administrator-representative would objectively achieve as a ressult of a careful management is the extent of the latter's responsibility in case he/ she neglects to obtain these profits. And for this responsibility, this person need not to be faulty. On the other hand,it also not taken into consideration whether the real person entitled intends to obtain thesa neglected profits.Ultimately, the person shall also be liable for having used the propertty personally. And as a result of his/ her using the property in person, the latter shall have to pay allowance for this using. Even though this liability has not been cleary stipulated in Article 995 of the Civil Law,it is imlied by the opposite meaning of Article 993.If the person unjustly in possession of the property has evil intention, the latter may just reguest the compulsory expenses. For this purpose,the compulsory expenses must have ensured that the real person entitled has become free of the costs and has saved them.
Keywords: Anayasa ve idare hukuku; Hukuk; Hukuk-Kamu Hukuku; Kamu Hukuku Türkiye